Volcanoes - Van Rose, Susanna; Mercer, Ian, 1944- ([Cambridge, Mass.] : Harvard, 1991)
Study of volcanoes with information on lava flow, historic eruptions, mud flows, and more.
Cover title.
Includes index.
Previous ed. published in 1974 by H.M.S.O. for the Institute of Geological Sciences, London.
University Press Titles (A.A.S.L./P.L.A.).
Wilson's Public Library.
Adult
Keywords: Volcanoes; Volcanoes